2019
DOI: 10.1371/journal.pone.0210904
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MnCo2O4 nanoparticles as modifiers for simultaneous determination of Pb(II) and Cd(II)

Abstract: The porous spinel oxide nanoparticles, MnCo2O4, were synthesized by citrate gel combustion technique. Morphology, crystallinity and Co/Mn content of modified electrode was characterized and determined by Fourier transform infra-red spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), X-ray diffraction pattern analysis (XRD), simultaneous thermogravimetry and differential thermal analysis (TG/DTA). Nanoparticles were used for modification of glassy carbon electrode (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…They were characterized by Fourier transform infra-red spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), X-ray diffraction pattern analysis (XRD) and simultaneous thermogravimetry and differential thermal analysis (TG/DTA). The results were published in our previous manuscript 34 .…”
Section: Preparation Of Working Electrodementioning
confidence: 85%
See 2 more Smart Citations
“…They were characterized by Fourier transform infra-red spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), X-ray diffraction pattern analysis (XRD) and simultaneous thermogravimetry and differential thermal analysis (TG/DTA). The results were published in our previous manuscript 34 .…”
Section: Preparation Of Working Electrodementioning
confidence: 85%
“…It exhibited high sensitivity, selectivity and wide concentration linear range for the determination of cadmium and lead. 34 The quantification of those analytes was interfered by copper ions and the signal for lead was decreased for about 40%, such behaviour was explained by the presence of the sulfate ions, and its effect on copper ions conductivity. For the wine samples, sulfuric acid was avoided, and the oxidation current for copper was significantly lower than for the lead even though it is abundant metal in the wine samples (Figure 1).…”
Section: Interferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Recently, Antunovićet.al reported that the citrate gel combustion technique assisted the synthesis of porous MnCo 2 O 4 spinel oxide for the simultaneous determination of Pb(II) and Cd(II) via linear sweep anodic stripping voltammetry. 10 This reveals itself in the sensing of cationic species and biomolecules using MnCo 2 O 4 spinel materials with surface effects and enhanced charge transfer.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Various spinel-type crystalline oxides (CoFe 2 O 4 , NiCo 2 O 4 , MnCo 2 O 4 , FeMnO 3 , NiMoO 4 , ZnFe 2 O 4 , and MnFe 2 O 4 ) have been employed for a wide range of applications, attracting a lot of attention. , Among them, manganese (Mn)-based nanomaterials have gained substantial attraction in many fields including optics, sensors, catalysis, electrochemical capacitors, and lithium-ion batteries. Manganese–cobalt oxide (MnCo 2 O 4 ), in particular, has enhanced structural and surface properties that can be attributed to the synergy between the constituents, making it a suitable candidate for sensing applications. , Zhang and co-workers have synthesized nanostructured MnCo 2 O 4 used for non-enzymatic glucose sensors. , Recently, Antunović et.al reported that the citrate gel combustion technique assisted the synthesis of porous MnCo 2 O 4 spinel oxide for the simultaneous determination of Pb­(II) and Cd­(II) via linear sweep anodic stripping voltammetry . This reveals itself in the sensing of cationic species and biomolecules using MnCo 2 O 4 spinel materials with surface effects and enhanced charge transfer.…”
Section: Introductionmentioning
confidence: 99%